The Idea of a Single Term of Office of the President and Vice President in Indonesia - Sahel Muzzammil; Fitra Arsil (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Limiting the term of office of the head of government is an important prerequisite for realizing a democratic state life. In Indonesia, these restrictions are imposed on the President and Vice President with a term of office of 5 years and after that, they can be re-elected only for 1 term of office. Using the normative juridical method, this study shows that this choice has become a source of debate in other parts of the world, and several presidential countries have chosen different models of restrictions. In Indonesia, it has been revealed that this choice is not based on a deep conceptual debate and empirically has threatened the continuity of a principled election. As a solution, this study offers the application of the concept of a single term of office for the President and Vice President in Indonesia. This research also enriches the study of state administration in the theme of structuring the presidential system.